Does crime affect economic decisions? An empirical investigation of savings in a high-crime environment - Jo\~ao M. P. De Mello; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2008)
While most economic studies of crime have focused on its determinants, we study the reverse question: does crime affect economic behavior? Being such an important social phenomenon, one would expect crime to affect economic decisions. Using local data on crime rates and savings per capita in a high-crime environment, we document a striking empirical relationship: crime induces savings. Our paper is one of the first to successfully relate crime to an economic outcome. This result is robust to an extensive sensitivity analysis, which include: 1) controlling to a large set of demographic covariates; 2) accounting for the fact that crime and savings may be determined jointly; 3) measuring savings in different ways; 4) accounting for the presence of possible outliers; 5) weighting the data according to population; 6) accounting for spatial correlation; and, finally, 7) estimating the model for different sub-samples of cities. Our estimates indicate that only property, not violent, crime induces savings, which is consistent with the theoretical explanations on why crime would increase thriftiness
Keywords: D00; D91; R11; Z19; 330; Crime; Economic Behavior; Savings; Kriminalität; Verhaltensökonomik